DEVELOPING LEADERSHIP COMPETENCE IN YOUNG LANGUAGE LEARNERS THROUGH INTERACTIVE METHODS - Risvayeva Charos Zaydilla qizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract. This article examines the importance of developing leadership competence among young language learners through interactive teaching methods. In modern education, language learning is no longer limited to acquiring grammatical knowledge and vocabulary. It also involves the development of communication, collaboration, critical thinking, and leadership abilities. Interactive methods such as group discussions, role plays, debates, project-based learning, and problem-solving activities create opportunities for learners to demonstrate initiative, responsibility, and teamwork. The study highlights how these methods contribute to building self- confidence, decision-making skills, and social interaction among students.